Counting nuclei released from microcarrier-based cultures using pro-fluorescent nucleic acid stains and volumetric flow cytometry - Michael Y.C. He; Steven A. Stacker; Ralph Rossi; Michael M. Halford (BioTechniques)
Counting nuclei released from intact cells is a convenient and reliable approach to assess cell density during microcarrier-based culture of adherent cells. However, commonly used methods for counting nuclei, such as crystal violet staining and quantification with a hemocytometer/ automated imaging system or a Coulter counter, are imprecise, laborious and, limited in throughput. Here, we describe the use of high-affinity pro-fluorescent nucleic acid stains and volumetric flow cytometry for automated counting of nuclei released from cells attached to microcarriers with improved precision and high sample throughput. This simple procedure facilitates rapid and precise assessment of cell attachment, survival, and proliferation on microcarriers, and can provide information about the cell cycle, all without the need for cell detachment. Consequently, various microcarrier-based applications, from small-scale multi-factor experiments to large-scale functional genetic screens and clinical/industrial cultures, could be enhanced by this approach.